2018
DOI: 10.1097/ccm.0000000000003349
|View full text |Cite
|
Sign up to set email alerts
|

Delirium Monitoring in Neurocritically Ill Patients: A Systematic Review*

Abstract: These data from studies of neurocritically ill patients demonstrate that patients with primary neurologic diagnoses can meet diagnostic criteria for delirium and that delirious features may predict relevant untoward clinical outcomes. There is a need for ongoing investigations regarding delirium in these complicated neurocritically ill patients.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

8
67
1
2

Year Published

2018
2018
2023
2023

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 75 publications
(83 citation statements)
references
References 67 publications
8
67
1
2
Order By: Relevance
“…In this prospective observational study, the delirium incidence of 18.7%, according to the diagnostic reference, was in accordance with the past reports with mostly neurovascular or trauma patients [8,15,21]. A similar delirium incidence in our more heterogeneous cohort may indicate that delirium occurs at largely similar frequencies in other neurological disorders with treatment on a neurocritical care unit.…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…In this prospective observational study, the delirium incidence of 18.7%, according to the diagnostic reference, was in accordance with the past reports with mostly neurovascular or trauma patients [8,15,21]. A similar delirium incidence in our more heterogeneous cohort may indicate that delirium occurs at largely similar frequencies in other neurological disorders with treatment on a neurocritical care unit.…”
Section: Discussionsupporting
confidence: 91%
“…In our cohort, we found low sensitivity (66.9%) and acceptable specificity (93.3%) for screening with CAM-ICU. Values were below those reported in a selected cohort of stroke patients by Mitasova and co-workers [16], but above those reported in other studies with neurological/neurosurgical patients [15,17,18,20]. The sensitivity (69.3%) and specificity (93.9%) of the ICDSC were comparable to those of CAM-ICU and similar to the findings in the study by Larsen and co-workers [20].…”
Section: Discussionsupporting
confidence: 77%
“…SDH patients tend to represent a very heterogeneous group, with considerable differences existing between acute and chronic hematomas in terms of their management, clinical manifestations, and outcomes; this supports the idea that RASS fluctuation may be more generalizable for patients with different types of brain injury. Finally, in order to have a comparison for RASS fluctuation, we used the CAM-ICU as a gold-standard delirium screen; this is a commonly used screen in neurologically ill patients, but has not been fully validated [7], and utilizes RASS scores for some of its criteria. A definitive study would need to compare RASS fluctuation to DSM-V criteria as the gold standard.…”
Section: Discussionmentioning
confidence: 99%
“…The study of delirium in neurologically critically ill patients has been limited in part because some studies have suggested a high rate of false positives in this population, particularly from new neurological injuries being misclassified as delirium [7]. This is unsurprising as many of the features of delirium can be seen with neurological injury; for example, prominent inattentiveness has been described with both thalamic injury [8] and frontal lobe injury [9], and non-convulsive seizures have been reported to present with delirium [10].…”
Section: Introductionmentioning
confidence: 99%
“…24 Notably, delirium can and often does coexist with underlying neurological disease such as dementia, traumatic brain injury, and stroke and so is not precluded from developing in these patients. 25,26 The incidence of delirium varies among individual studies but is a frequent diagnosis in all inpatient care settings. Vasilevskis and colleagues estimated that approximately one-third of patients who were hospitalized ultimately developed delirium.…”
Section: Manifestations and Outcomes Of Icu Delirium Manifestationsmentioning
confidence: 99%